Peran Perilaku Berkelanjutan dalam Manajemen Lingkungan untuk Pengembangan Desa Wisata Berbasis Energi Terbarukan - Syamsul Ma'arif; Rini Eka Sari; Nurul Myristica Indraswari (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
This study examines the crucial role of sustainable behavior in environmental management for the development of renewable energy-based tourism villages. Sustainable behavior is of utmost importance in creating economically, socially, and environmentally sustainable tourism villages. The aim of this research is to integrate the concepts of sustainable behavior, environmental management, and renewable energy-based tourism village development. The research method employed is a literature review, focusing on relevant scholarly articles published in English or Indonesian after 2018. The findings indicate that sustainable behavior plays a significant role in environmental management within tourism villages, through the sustainable management of natural resources and the implementation of practices that support sustainability. The utilization of renewable energy sources in tourism village development also has positive impacts on the environment. By adopting sustainable behavior, renewable energy-based tourism villages have the potential to serve as inspiring examples in sustainable tourism development that prioritizes environmental preservation and the well-being of local communities. Furthermore, further actions are needed, including educational programs, stakeholder partnerships, the use of sustainable infrastructure, and the empowerment of local communities within the context of renewable energy-based tourism village development.